Racial and ethnic disparities in early treatment with immunotherapy for advanced HCC in the United States. Issue 6 (27th April 2022) - Ahn, Joseph C.; Lauzon, Marie; Luu, Michael; Noureddin, Mazen; Ayoub, Walid; Kuo, Alexander; Sundaram, Vinay; Kosari, Kambiz; Nissen, Nicholas; Gong, Jun; Hendifar, Andrew; Roberts, Lewis R.; et al.
Abstract: Background and Aims: Immunotherapy has emerged as an effective treatment for patients with advanced‐stage HCC. We aimed to investigate the efficacy of immunotherapy for advanced HCC in a nationwide cohort and racial and ethnic disparities in access to immunotherapy. Approach and Results: We used the US National Cancer Database to identify patients with tumor‐node‐metastasis stage 3 or 4 HCC between 2017 and 2018. We performed multivariable Cox regression to identify factors associated with overall survival (OS) and logistic regression to identify factors associated with receipt of immunotherapy. Of the 3, 990 patients treated for advanced HCC, 3, 248 (81.4%) patients received chemotherapy and 742 (18.6%) patients received immunotherapy as a first‐line treatment. Immunotherapy was associated with improved OS compared with chemotherapy (adjusted HR: 0.76, 95% CI: 0.65–0.88) after adjusting for covariates. There were racial and ethnic disparities in access to immunotherapy, with Hispanic (adjusted OR [aOR]: 0.63, 95% CI: 0.46–0.83) and Black patients (aOR: 0.71, 95% CI: 0.54–0.89) less likely to receive immunotherapy compared with White patients. There was a significant interaction between race‐ethnicity and facility type, with higher disparity observed in nonacademic centers (interaction p = 0.004). Conclusions: Immunotherapy was associated with improved OS compared with chemotherapy in advanced HCC. There are significant disparities in early access to immunotherapy, likely due to differential access to clinical trials and experimental therapies. A comprehensive approach to monitoring and eliminating racial‐ethnic disparities in the management of advanced HCC is urgently needed. Abstract : In a retrospective analysis of the US National Cancer Database, immunotherapy was associated with improved overall survival compared to chemotherapy in patients with advanced HCC, but significant racial/ethnic disparities in early access to immunotherapy were observed.image